2022
DOI: 10.3390/ijms23052710
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Phosphoribulokinase Amount and Re-Routing Metabolism in Chlamydomonas reinhardtii CP12 Mutants

Abstract: The chloroplast protein CP12 is involved in the dark/light regulation of the Calvin–Benson–Bassham cycle, in particular, in the dark inhibition of two enzymes: glyceraldehyde−3-phosphate dehydrogenase (GAPDH) and phosphoribulokinase (PRK), but other functions related to stress have been proposed. We knocked out the unique CP12 gene to prevent its expression in Chlamydomonas reinhardtii (ΔCP12). The growth rates of both wild-type and ΔCP12 cells were nearly identical, as was the GAPDH protein abundance and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…This suggests that CP12 is involved in the post-translational regulation and at the transcriptional level. A recent study showed that reduced C. reinhardtii CP12 stabilizes PRK in vitro and in vivo, but the mechanism of this protection needs further investigation [ 76 , 77 ]. In the mutant strain of C. reinhardtii , where the CP12 protein is absent, while the abundance of numerous proteins increases (see below), the abundance of others, including PRK, involved in photosynthesis, decreases.…”
Section: One Gene One Protein Many Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that CP12 is involved in the post-translational regulation and at the transcriptional level. A recent study showed that reduced C. reinhardtii CP12 stabilizes PRK in vitro and in vivo, but the mechanism of this protection needs further investigation [ 76 , 77 ]. In the mutant strain of C. reinhardtii , where the CP12 protein is absent, while the abundance of numerous proteins increases (see below), the abundance of others, including PRK, involved in photosynthesis, decreases.…”
Section: One Gene One Protein Many Functionsmentioning
confidence: 99%
“…In C. reinhardtii , the deletion of the protein induced a re-routing of the metabolism under the light. In particular, metabolic pathways involving malate shuttles increased in the mutant such as the tricarboxylic acid cycle (TCA) and the glyoxylate pathway [ 77 ]. Malate shuttles, combined with other signaling factors, play a putative role in algal CO 2 -concentrating mechanisms (CCM) [ 82 , 83 ].…”
Section: One Gene One Protein Many Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the N-terminal region of CP12 containing one cysteine pair followed by the consensus sequence binds PRK. In the eukaryotic alga Chlamydomonas reinhardtii , the core sequence of CP12 was found to act in the formation of the GAPDH–CP12–PRK complex and the protection of PRK from irreversible inactivation in vitro ( Gérard et al, 2022 ). In the light, complex dissociation mediated by CP12 reduction via a thioredoxin allows GAPDH and PRK reactivation, and consequently CO 2 fixation ( Gurrieri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%